Hapten-labeled DNA probes can be stored and used in fluorescence in situ hybridization for decades - Liehr, Thomas; Padutsch, Niklas; Kankel, Stefanie (Frontiers in Genetics, 2025)
In molecular cytogenetics, fluorescence in situ hybridization (FISH) is the main technique used. In both research and diagnostics, FISH depends on well-defined and mapped DNA probes that produce brilliant signals with minimal background, visible in metaphases and/or interphases. Such probes are either ready-to-use and commercially available or provided as unlabeled DNA. The latter can be obtained by flow sorting, microdissection, or by cloning DNA segments into appropriate bacterial vectors. Labeling can be done with either nonfluorescent or fluorescent haptens. According to international guidelines, such FISH probes must have a minimum shelf life, which is only between 2 and 3 years in human genetic diagnostics. The Molecular Cytogenetics Laboratory reporting here has been purchasing, producing, using, and storing FISH probes since the 1990s. For this study, the available stock of approximately 25,000 labeled probes was screened. A total of 581 FISH probes, labeled and approved 1–30 years before reuse, were selected for this study; of these, 75 were commercially available probes labeled 1–20 years ago. All of these probes, stored in the dark at −20°C, worked perfectly well in the FISH method. Although only slight to no differences in exposure times were observed over the years for self-labeled homemade probes, commercial probes labeled with SpectrumOrange had shorter exposure times and maintained them over the years. DNA probes labeled with SpectrumAqua/diethylaminocoumarin showed bright labeling for the first 3 years and then faded. Accordingly, it can be assumed that self-labeled homemade and commercial FISH probes can be stored stably in the dark and at −20°C for at least 30 years or longer. There is no need to test approved probes on a slide after the official expiry date. In practice, this suggests that a FISH probe tube that has been approved can be used in diagnostics until it is empty; there is no need to dispose of these expensive probes at any point due to their age.